Statin exposure and risk of colorectal cancer in patients with inflammatory bowel disease: a systematic review and meta-analysis - Li, Ai-juan; Jiang, Hai-yin; Jia, Yong-hui (Frontiers in Medicine, 2024)
No ethical approval was required for this review as all data were already published in peerreviewed journals.AJL and YHJ searched the library and wrote the manuscript text. YHJ and HYJ extracted data and reviewed all articles. AJL designed the manuscript. All authors reviewed the manuscript.Background: While epidemiological studies have linked statin use to a reduced risk of advanced colorectal adenomas, its impact on colorectal cancer (CRC) risk in patients with inflammatory bowel disease (IBD) remains unclear. To our knowledge, no meta-analysis to date has specifically examined this association. Therefore, we conducted a systematic review and metaanalysis of the available observational studies to investigate the risk of CRC associated with statin use in IBD patients.We searched three databases for articles published in English before September 2024, focusing on the protective effects of statins against CRC in IBD patients. We calculated multivariate odds ratios (ORs) and their 95% confidence intervals (CIs) to assess this association.A random-effects meta-analysis was conducted using the generic inverse variance method.The meta-analysis included 4 studies encompassing 22,250 IBD patients, 6,712 of whom were statin users. The methodological quality of three of the studies was deemed high. We found a significantly lower risk of CRC in statin users compared to non-users, with a pooled relative risk of 1.88 (95% CI 1.54-2.30). Sensitivity analyses confirmed the consistency of these findings.Statin use appears to be associated with a reduced risk of CRC in patients with IBD.However, given the limited number of studies available, further prospective research with large sample size is necessary to confirm the potential chemopreventive role of statins in this population.